Afforestation Drives Soil Carbon and Nitrogen Changes in China - Deng, Lei; Shangguan, Zhou‐ping (Land degradation & development, 2017)
Afforestation has been proposed as an effective method of carbon (C) sequestration; however, the magnitude and direction of soil C and nitrogen (N) dynamics following afforestation are not well understood. This study was designed to examine soil C and N dynamics following afforestation and to determine how various factors affect soil organic C (SOC) and total N (TN) after land‐use conversions through the compilation and analysis of published data from 61 individual studies (512 observations at 61 sites in China). This analysis showed that for different previous land uses, post‐afforestation SOC, TN, and C/N ratio varied in diverse temporal patterns. The relationship of soil C–N coupling was related to land use prior to afforestation and forest age. At 0–100 cm soil depths, SOC and TN increased at rates about 0·23 and 0·03 g kg−1 y−1, respectively, and the C/N ratio was about 0·19 y−1. SOC and TN were significantly affected by tree species, forest age, and soil depth. SOC, TN, and C/N were negatively correlated with soil bulk density (p < 0·01) and pH (p > 0·05) but positively correlated with soil total phosphorus (p < 0·01), soil moisture (p < 0·01) and soil microbial biomass C (p < 0·01) and N (p < 0·01). Additionally, SOC and TN were higher for the mid‐level humidity index in China and were also determined by precipitation, temperature, and forest age. These results highlight the importance of previous land use, tree species, soil depth, and forest age in determining soil C and N changes in a range of environments and land‐use transitions. Copyright © 2016 John Wiley & Sons, Ltd.